KEGUNAAN TERJEMAH QUR'AN BAGI UMMAT MUSLIM - Juairiah Umar (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2017)
Al-Qur'anul Karim is an everlasting Islamic miracle and reinforced by the advancement of science. He revealed Allah to the Messenger s.a.w. To bring people from darkness to light, and guide them to a straight path. Al-Qur'anul Karim was revealed to the Holy Prophet with a clear Arabic language. This phenomenon is a social demand for the success of Islamic pamphlets. And since that time Arabic became a part of Islamic existence and the basis of communication of its dakwah. The mission of our Apostle is to all mankind. The Qur'an is essential in many languages to be easily understood by Muslims. Every Muslim community needs to know the asbabun nuzul, so there is no mistake in overcoming the verses of the Qur'an. The purpose of translating the Qur'an is to know the meaning of the contents in the Qur'an, can help memorize the Qur'an by understanding the meaning. For translators Al-Quran need to master two languages, the original language (source language) and the language of translation, the language style and the privileges of both languages.